Inokulasi Bakteri Selulolitik Actinobacillus sp. Asal Rumen pada Daun Jati Menurunkan Serat Kasar dan Meningkatkan Protein Kasar - Lamid, Mirni; Julita, Anggun Foetus Eka; Widjaya, Ngakan Made Rai (Jurnal Veteriner, 2013)
Constraints use teak leaves as ruminant feed is a high content of crude fiber and low crude protein.The objective of this research was to determine potency of inoculation  Actinobacillus sp. of rumen productionon teak leaves fermentation process could improve quality of teak leaves as animal feed for ruminants.Design study was Completely Randomized Design with four treatments and five replications. Fourtreatment groups were consist of  : P0 = teak leaves + 2% molasses (control); P1 = teak leaves + 2%molasses + 5% Actinobacillus sp.;  P2 = teak leaves + 2% molasses + 10% Actinobacillus sp.;  P3 = teakleaves + 2% molasses + 15%  Actinobacillus sp. Proximate analysis were done after teak leaves werefermented for seven days. The data were analyzed with Analysis of Variance followed by Duncan’s MultipleRange Test. The results showed a significant difference (P <0.05) for crude fiber and crude protein P3 andP2 compared with control’s. Crude fiber content of P3 and P2 respectively 31.67% and 32%, while the crudeprotein content of P3 and P2 respectively 13.57% and 13.31%. Conclusions of this research are:  InoculationActinobacillus sp. with doses 5%, 10% and 15% in the fermentation teak leaves can decrease crude fibercontent and increased crude protein content. Dose efficient to use bacterial fermentation teak leavesActinobacillus sp. is 10%.
Keywords: Actinobacillus sp, fermented, teak leaves, crude fiber, crude protein